(untitled) (Análisis Económico, 2018)
The aim of this paper is to test for the existence of a wage curve for the Spanish economy between 1994 and 1996. The results confirm the negative relation between the level of nominal wages and the unemployment rate in local labor markets. We also analyse whether there is a relation between the local unemployment rate and wage changes, as the Phillips curve describes, with disaggregated data, introducing the lagged dependent variable into the specification and check the value of its coefficient. The results do not permit us to affirm that there is evidence of a Phillips curve relation. JEL Classification: J31, J60, J69.